Concurrent Disruption of Genetic Interference and Increase of Genetic Recombination Frequency in Hybrid Rice Using CRISPR/Cas9 - Liu, Chaolei; Cao, Yiwei; Hua, Yufeng; Du, Guijie; Liu, Qing; Wei, Xin; Sun, Tingting; Lin, Jianrong; Wu, Mingguo; Cheng, Zhukuan; Wang, Kejian (Frontiers in Plant Science, 2021)
Manipulation of the distribution and frequency of meiotic recombination events to increase genetic diversity and disrupting genetic interference are longstanding goals in crop breeding. However, attenuation of genetic interference is usually accompanied by a reduction of recombination frequency and subsequent loss of plant fertility. In the present study, we generated null mutants of the ZEP1 gene, which encodes the central component of the meiotic synaptonemal complex (SC), in a hybrid rice using CRISPR/Cas9. The null mutants exhibited absolute male sterility but maintained nearly unaffected female fertility. By pollinating the zep1 null mutants with 93-11 pollen, we successfully conducted genetic analysis and found that genetic recombination frequency was greatly increased and genetic interference was completely eliminated in the absence of ZEP1. The findings provided direct evidence to support the controversial hypothesis that SC is involved in mediating interference. Additionally, the remained female fertility of the null mutants makes it possible to break linkage drag. Our study provides a potential approach to increase genetic diversity and fully eliminate genetic interference in rice breeding.